Analysis on Online Hotel Review System using Opinion Mining in Question Answering system - K. Karpagam , V. J. Chakravarthy , V.R.Niveditha , K. Amandeep singh ,V.Vinoth Kumar (International Journal of Advanced Science and Technology, 2020)
The online hotel review system has become more popular platform for sharing customer review which supports better travelling experience and customer satisfaction. Enormous customer reviews posted to internet with respect to time zones. Hotel review content has been analyzed with sentimental analysis through a learning model which train and tested by benchmark dataset Tripadvisor. Score based algorithm use to compute the high rated semantically related reviews. The proposed framework is used to design and develop of chatbot for disseminating information about best hotel through opining mining. It is capable of answering user queries about the 278 hotels in Newdelhi with 5191 customer reviews. Experiments conducted and evaluated with standard metrics is to assess the performance and efficiency of the system. From the results, it has proven that the system outer performs than existing systems in producing the best hotel using customer hotel review.